Does medieval trade still matter? Historical trade centers, agglomeration and contemporary economic development - Fabian Wahl (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
This study empirically establishes a link between medieval trade, agglomeration and contemporary regional development in ten European countries. It documents a statistically and economically significant positive relationship between prominent involvement in medieval trade and commercial activities and regional economic development today. Further empirical analyses show that medieval trade positively influenced city development both during the medieval period and in the long run; they also reveal a robust connection between medieval city growth and contemporary regional agglomeration and industry concentration. A mediation analysis indicates that a long-lasting effect of medieval trade on contemporary regional development is indeed transmitted via its effect on agglomeration and industry concentration. This research thus highlights the long-run importance of medieval trade in shaping the development of cities as well as the contemporary spatial distribution of economic activity throughout Europe. The path-dependent regional development processes caused by medieval commercial activities help explain the observed persistent regional development differences across the European countries considered.
urn:nbn:de:bsz:100-opus-8954
Keywords: F14; N73; N93; O18; R12; 330; Medieval Trade; Agglomeration; Regional Economic Development; Path-Dependency; New Economic Geography